Spatial scales in alluvial channels: on 2d coherent turbulent structures and alternate bars formation - Carrasco Milian, Aylen (2012)
Fil: Carrasco Milian, Aylen. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.